2005
DOI: 10.1002/zamm.200310222
|View full text |Cite
|
Sign up to set email alerts
|

Stability of two superposed viscoelastic fluid‐particle mixtures

Abstract: The stability of the plane interface separating two viscoelastic (Walters B′) superposed fluids of uniform densities in the presence of suspended particles is considered. The stability analysis has been carried out, for mathematical simplicity, for two highly viscoelastic fluids of equal kinematic viscosities and equal kinematic visco‐elasticities. For the (density wise) stable configuration, the system is found to be stable or unstable for the wave number range k ≤ or > \documentclass{article}\usepackage{amss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In the presence of "effective interfacial tension" in accordance with (18), there will be stability if i.e.…”
Section: Case Ii: In the Presence Of Effective Interfacial Tensionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the presence of "effective interfacial tension" in accordance with (18), there will be stability if i.e.…”
Section: Case Ii: In the Presence Of Effective Interfacial Tensionmentioning
confidence: 99%
“…Kumar [17], considered the thermal instability of a layer of a Walters B′ viscoelastic fluid acted on by a uniform rotation and found that for stationary convection, rotation has a stabilizing effect. Kumar, et al [18], considered the stability of the plane interface separating two Walters B′ viscoelastic superposed fluids of uniform densities in the presence of suspended particles. The medium was non-porous in all the above studies.…”
Section: Introductionmentioning
confidence: 99%
“…Kumar 6 investigated the impact of rotational forces on the thermal instability of Walter’s B fluid, while Sharma et al 7 scrutinized the stratified Walter’s B fluid within a porous medium, in conjunction with the interplay between rotation and magnetic field. Furthermore, the suspended particle effect on the stability of superimposed Walter’s B fluid was expatiated upon by Kumar et al, 8 whereas Kumar and Lal 9 researched the RayleighTaylor (R-T) instability at the interface between Newtonian and Walter’s B fluid.…”
Section: Introductionmentioning
confidence: 99%
“…Kumar (2001) considered the thermal instability of a layer of a Walters B' viscoelastic fluid acted on by a uniform rotation and found that for stationary convection, rotation has a stabilizing effect. Kumar et al (2006) considered the stability of plane interface separating the Walters B' viscoelastic superposed fluids of uniform densities in the presence of suspended particles.…”
Section: Introductionmentioning
confidence: 99%